Integrating sustainability in business process modeling - Ida Hindarsah (SEAN Institute, 2024)
Sustainability is becoming increasingly important in the modern business context, where organizations are increasingly aware of the ecological and social impacts of their operations. This research will focus on developing an approach that allows business process modeling to not only take operational efficiency into account, but also include sustainability dimensions. This research uses a qualitative approach with descriptive methods. The research results show that integrating sustainability in business process modeling plays a key role in shaping a company's sustainability and success. Sustainable business models, which take into account economic, social and environmental aspects, not only increase financial value, but also create a positive impact on employees, consumers and the environment. An inclusive approach to company ownership can address the wage gap and create a fair work environment. Going green, while it may increase the price of a product, can improve a brand's reputation by engaging consumers in discussions about sustainability.